2020
DOI: 10.3390/medicina56050217
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Magnetic Resonance Imaging as a Noninvasive Parameter for Differentiating Benign and Malignant Intraperitoneal Collections

Abstract: Background and Objective: The imaging differentiation of benign from malignant intraperitoneal collections (IPCs) relies on the tumoral morphological modifications of the peritoneum, which are not always advocating for malignancy. We aimed to assess ascitic fluid with the apparent diffusion coefficient (ADC) to determine non-invasive, stand-alone, differentiation criteria for benign and malignant intraperitoneal effusions. Materials and Methods: Sixty-one patients with known IPCs who underwent magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…We previously demonstrated that the quantitative imaging parameters could increase the confidence in diagnosing malignancy-related ascites. Both commonly used quantitative measurements, such as Hounsfield units [ 44 ], apparent diffusion coefficients [ 45 ], but especially TA-derived parameters on CT [ 46 ] and MRI [ 47 ], were demonstrated to function as a non-invasive criterion that can aid the discrimination of benign and malignant intraperitoneal fluid collections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that the quantitative imaging parameters could increase the confidence in diagnosing malignancy-related ascites. Both commonly used quantitative measurements, such as Hounsfield units [ 44 ], apparent diffusion coefficients [ 45 ], but especially TA-derived parameters on CT [ 46 ] and MRI [ 47 ], were demonstrated to function as a non-invasive criterion that can aid the discrimination of benign and malignant intraperitoneal fluid collections.…”
Section: Discussionmentioning
confidence: 99%
“…The potential use of texture analysis to reflect histology and microstructure of malign ascites has been thoroughly proved for oncologic imaging [ 43 , 45 , 46 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The b-value is a factor that mirrors the timing and strength of the gradients utilized to generate these sequences [ 39 ]. The DWI images are computed by turning diffusion-sensitizing gradients at various strengths [ 40 ], and the b-value is directly linked to the diffusion effects [ 39 ]. Our ADC measurements show that non-mucinous lesions had lower values than mucinous, which may seem counterintuitive at first glance.…”
Section: Discussionmentioning
confidence: 99%
“…ADC fluctuations between slices in abdominal MRI were observed by Miquel et al [ 53 ], who conclusively proved that these variations are much less likely to influence three-dimensional (3D) VOIs because any differences between (and within) slices are likely to be averaged over the large VOI. In- and interslice averaging does not occur with 2D ROIs, but this method has the advantage of higher reproducibility coefficients compared with the 3D analysis [ 40 , 53 ]. We agree that using VOIs would have offered a more “comprehensive” description of diffusion within the collections, while also accounting for within- and between-slice variations.…”
Section: Discussionmentioning
confidence: 99%